Pelaksanaan Pencegahan Covid-19 pada Keluarga Ibu Hamil, Bersalin dan Nifas di Wilayah Kerja Puskesmas II Denpasar Barat - Idah Ayu Wulandari; Ni Wayan Manik Parwati (Poltekkes Kemenkes Denpasar, 2021)
Covid-19 is an infectious disease and attacks the human respiratory system. Pregnant, delivery dan post partum mother are groups that are vulnerable to contracting Covid-19. If the mother is infected by Covid-19, the baby who is born later and the baby who is being breastfed have the potential to be infected. Therefore, family support in supporting the implementation of prevention of transmission is needed. This study aims was to determine the implementation of the prevention of Covid-19 in the families of pregnant, delivery and postpartum mothers. This research was a descriptive study with a cross sectional design. The population in this study were all families of pregnant, delivery and post-partum mothers in the West Denpasar II Community Health Center’s area, all of the participants are 112 people who were taken by purposive sampling technique. Data analysis was performed using descriptive statistics. The results showed that most respondents who were families of pregnant, delivery and postpartum mothers in this study had well behaviour about prevention Covid-19 (72.3%). It is hoped that the community, especially those around the mother, should always carry out the prevention of COVID-19 and reprimand if there are people who do not take actions that prevent Covid-19